Instrumentos de magia e de ciência: a observação mediada em De telescopio segundo a perspectiva de Giambattista della Porta - Saito, Fumikazu (2008)
This work discusses the relationship between instrument and sensorial or perceptive experience in the light of Giambattista della Porta s natural magic and the 17th century natural philosophy. It points out to factors that made of the telescope a natural magic device, by approaching to the design of Galileo Galilei s instrument. Analysis is centered on De telescopio, De refractione optices parte libri novem and Magiae naturalis libri XX by Della Porta and Sidereus nuncius by Galileu, as primary sources. This study allowed to realize that the expansion of the visual capacity achieved through instruments and devices was not merely related to philosophical strategies that would lead to mistrust naked-eye observation or mathematization of seeing by 15th century linear perspective. Among other features involved in the change of views regarding the observation of nature, the recognition of the sharper visual perception achieved through instruments was also associated to natural magic s manipulation of seeing